ANALYSIS OF APPOINTMENT DECREES IN THE KHANATE OF KHIVA (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
As is known, matters concerning appointments have historically developed and refined under the influence of statehood traditions, political considerations, and legal norms. In this process, appointment to office was formed not only as an administrative act but also as a means of strengthening the system of state power and governance and of regulating social relations. Therefore, researching this aspect based on legislative documents issued by the Khiva Khanate’s court chancellery makes it possible to gain a deeper scientific understanding of the history of statehood. In the state administration system of the Khiva Khanate, the institution of offices and the practice of appointments to them were considered an important component of political and legal relations. In particular, appointments decrees are of special importance as a source for studying the practical functioning of state administration, the rights and duties of officials, as well as the legal foundations of the khan’s authority. This is because the edicts, issued by the ruling class (the khan, governors, princes), are considered important in state administration as legal acts that are strict, immutable, and universally binding.